The Role of Investment Decisions, Financing Decisions, and Dividend Policy on Financial Performance - Ayu Yudiani Lestari; Badie Uddin; Loso Judijanto; Yudi Supiyanto; Dina Diana (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The research explores the influence of investment decisions, financing decisions, and dividend policy on the financial performance of companies listed on the LQ45 index of the Indonesia Stock Exchange during the 2021–2024 period. In the face of fluctuating macroeconomic conditions post-COVID-19, the study emphasizes the importance of these financial decisions in shaping corporate outcomes. The objective is to provide empirical insights into how these factors contribute to the overall financial performance, particularly in an era of economic uncertainty. A qualitative approach was employed, utilizing a literature study design based on secondary data from journals, books, financial reports, and company annual reports. The findings reveal that companies making strategic investment decisions, particularly in technology and innovation, are more likely to experience improved financial performance, as seen in the case of PT Telekomunikasi Indonesia Tbk. Furthermore, financing decisions, especially those managing a balanced capital structure, significantly impact profitability, with examples like PT Astra International Tbk leveraging debt effectively. Lastly, a consistent and balanced dividend policy contributes to strong investor confidence, thereby enhancing financial performance. The study concludes that companies can optimize their financial performance by carefully balancing investment, financing, and dividend decisions.